Carbon flux distribution in the metabolism of Shimwellia blattae (p424IbPSO) for isobutanol production from glucose as function of oxygen availability. Issue 3 (19th November 2018) - Acedos, Miguel G; Yustos, Pedro; Santos, Victoria E; Garcia‐Ochoa, Felix
Abstract: BACKGROUND: The carbon flux distribution in Shimwellia blattae (p424IbPSO) cultures when glucose is employed as carbon source is studied in a stirred tank bioreactor changing the oxygen availability. The strain has been constructed to produce isobutanol combining the branched‐chain amino acids pathway and Ehrlich pathway. The information of many similar genetic modified strains for this bioprocess in the literature presents significant discrepancies on the oxygen influence. RESULTS: The study carried out in this work pointed out the presence of other metabolites formed under aerobic conditions, such as isobutyric acid, 2, 3‐butanedione, acetoin, 2, 3‐butanediol and 3‐oxo‐1‐buten‐2‐yl ether, not previously reported in the literature on the production of isobutanol with S. blattae (p424IbPSO) strain. CONCLUSION: In this work the routes or the chemical reactions involved in the bioprocess as a function of the availability of oxygen are elucidated. Anaerobic conditions are the best for isobutanol production from glucose employing this strain; around 12 g L −1 of isobutanol are obtained under these conditions. Aerobic conditions are not adequate to produce isobutanol, although the need for oxygen, at least for growth, is also demonstrated. © 2018 Society of Chemical Industry